2021
DOI: 10.1037/pag0000585
|View full text |Cite
|
Sign up to set email alerts
|

Age-related change in self-perceptions of aging: Longitudinal trajectories and predictors of change.

Abstract: Using data from the German Ageing Survey (Deutscher Alterssurvey, DEAS; N = 4,712), this study examined age-related change in three dimensions of self-perceptions of aging (SPA): perceptions of physical losses, social losses, and ongoing development. Participants ranged in age from 40 to 85 years at study entry (1996, 2002, or 2008) and were followed for up to 21 years. Time-invariant, context-specific and timevarying, person-specific predictors of the observed age-related changes were examined. Findings from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 90 publications
5
63
0
Order By: Relevance
“…In contrast, an older subjective age, higher perceptions of social loss, physical decline, as well as lower perceptions of continuous growth had a negative impact on subsequent perceived stress that was—in our sample of middle-aged and older adults—independent of age (although the age interaction effect for perceptions of physical decline was close to statistical significance, p = .051). Perceptions of continuous growth might be the domain among the aging-related cognitions with the least “age salience” (with items such as continuing to make plans and still learning new things) and that is perhaps more dependent on factors such as positive affect (Diehl et al, 2021) or personality-related characteristics (e.g., optimism, self-efficacy, hope; Spuling et al, 2019; Steverink et al, 2001) than on chronological age. Subjective age might again be different from most other views on aging indicators in its relation to stress as subjective age ratings are usually not (or not only) based on a cognitive-evaluative process, other than ratings for the items of ATOA or of the aging-related cognitions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, an older subjective age, higher perceptions of social loss, physical decline, as well as lower perceptions of continuous growth had a negative impact on subsequent perceived stress that was—in our sample of middle-aged and older adults—independent of age (although the age interaction effect for perceptions of physical decline was close to statistical significance, p = .051). Perceptions of continuous growth might be the domain among the aging-related cognitions with the least “age salience” (with items such as continuing to make plans and still learning new things) and that is perhaps more dependent on factors such as positive affect (Diehl et al, 2021) or personality-related characteristics (e.g., optimism, self-efficacy, hope; Spuling et al, 2019; Steverink et al, 2001) than on chronological age. Subjective age might again be different from most other views on aging indicators in its relation to stress as subjective age ratings are usually not (or not only) based on a cognitive-evaluative process, other than ratings for the items of ATOA or of the aging-related cognitions.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with depressive symptoms and high negative affectivity, in turn, tend to display, according to Beck’s cognitive theory of depression the negative cognitive triad (Beck et al, 1987), that is, a negative view of themselves, of the world, and of the future, which potentially also includes the perceptions and anticipations of their aging. Indeed, higher negative affect as well as higher depressive symptomatology were found to predict less favorable views on aging (Diehl et al, 2021; Kotter-Grühn, 2015; Schönstein et al, 2021). Moreover, Bellingtier et al (2017) indeed found that negative affect is a mediator of the association between stressors and subjective age.…”
Section: The Need For a Multi-indicator Perspective On Views On Agingmentioning
confidence: 97%
See 1 more Smart Citation
“…Together, these results imply that perceiving late life as a phase of growth ( Huxhold, 2019 ) may motivate individuals to not only maintain existing bonds but also to form new ties (particularly non-kin ties). However, a recent study demonstrated that self-perceptions of aging become increasingly more negative with advancing age ( Diehl et al, 2021 ). In particular, the perception of aging as being associated with the potential for growth declined steeply after the age of 70.…”
Section: The Dire Modelmentioning
confidence: 99%
“…Response options for both items range from 1 "Not at all" to 4 "Almost everyday" and the depression score is based on their average. These covariates were selected given their past association with various measures of ageism (Ayalon, 2013;2018;Diehl et al, 2021).…”
Section: G R O U P M E M B E R S H I Pmentioning
confidence: 99%